Kekuatan Hukum Covernote Notaris Dalam Proses Takeover Perjanjian Kredit - Sean, Cedric; Uktolseja, Novyta; Haliwela, Nancy Silvana (KANJOLI Business Law Review, 2023)
with the debtor or something related to the Notary's Duties and Authorities in accordance with Law Number 30 of 2004. One form of Notary authority over the Credit agreement is by issuing a Covernote. In fact, Covernote is not regulated in the Law, so it is necessary to review the legal force of Covernote. Notary in Credit process at Banks and how the legal consequences of Notary Covernote on Debtors and Creditors. To know and explain, related to the form of Notary Covernote Legal Power in the Credit Agreement Takeover Process. Normative juridical methods, which will certainly be studied more deeply based on positive legal provisions, as well as legal principles. as well as using primary, secondary and tertiary legal materials. From the results of the study, it is known that Notary Covernote in terms of credit disbursement by the Bank to its customers serves only as a bank handle. Covernote as a notary legal product has no legal effect, because Covernote is not an authentic deed or a separate deed, but only an ordinary letter explaining the ability or notary information to complete the unfinished process. Notary negligence in fulfilling what is stated in the Covernote will cause losses / legal consequences for the bank as a creditor where the guarantee engagement can be considered a failure, while the credit agreement is still ongoing, and on the debtor side it will incur new costs if re-engagement must be made, and also the notary can be criminally prosecuted, if it turns out that in making the Covernote there is an element of notary negligence on the validity and correctness of the document. So to avoid this, a legal umbrella / law is needed that regulates the use / issuance of Covernote to protect the interests of banks, debtors and limited against notaries.